Parental satisfaction with waiting time in a Swiss tertiary paediatric emergency department. Issue 8 (21st December 2020) - Löflath, Viola; Hau, Eva-Maria; Garcia, Daniel; Berger, Steffen; Löllgen, Ruth
Abstract : Introduction: Patient numbers in paediatric emergency departments (PED) are steadily increasing. Parental perception of waiting time and reasons for attending a PED with non-emergencies have been investigated in the UK, Australia, Korea, Canada and the USA. We sought to examine which factors influence parental satisfaction with waiting time in a tertiary Swiss PED and whether these differed from other countries. Methods: Paper surveys were administered to parents of children presenting to our interdisciplinary PED from February to May 2015. Primary outcome was parental satisfaction with waiting time, secondary outcomes were satisfaction with treatment, parental reasons for presentation with non-emergencies, parental perception of times to triage, first physician contact and disposition from ED, level of physician training, understanding of various anticrowding strategies and comparison of perceived and true waiting times to triage and physician contact. Results: 739 out of 750 surveys were returned (57 complete, 298 with 1 or 2 missing answers). Satisfaction with waiting time (on a 5-point-Likert-scale; 1 being the best possible answer) was higher in groups with shorter waiting time until triage (+0.41, p=0.001), first physician contact (+1.43, p<0.001) and discharge (+0.71, p<0.001), higher triage category urgency (+0.47, p=0.044) and available entertainment (+0.82, p<0.001). Early first physician contact (+0.33, p=0.008) and time to discharge less than 4 hours (+0.37, p<0.001) was associated with greater satisfaction with treatment (p<0.05). The most frequent reasons for presentation were parental impression that the child had an emergency (n=265, 35.9%) and referral by the family doctor (n=245, 33.2%). Conclusion: To counteract parental dissatisfaction associated with waiting time, we suggest the implementation of feasible measures including entertainment while waiting, early first medical review and timely discharge from the PED.